Auditing standards in Malaysia - Heng, Ji Keng (Penerbit Universiti Kebangsaan Malaysia, 1982)
The audit profession in Malaysia today faces many problems; the most urgent of which is the apparent lack of professional standards by some auditors in the conduct of their audits.The problem is further aggravated by the lack of legal or professional sanction on the auditors in the face of massive audit failures. This is no blessing to the image of the audit as well as the accounting profession as a whole, as the audit function forms the vel)' backbone of the accounting profession. It is the audit function that has given the accounting profession the prestige and the professional status that it currently enjoys and it is the independent audit function which has distinguished the accounting profession from the other related professions in the fields of information systems such as management consultants, computer experts and statisticians.